Innovative development of the road and transport complex: problems and prospects - Levchenko, Iaroslava; Dmytriiev, Illia; Beketov, Yuriy; Britchenko, Igor; Bekmukhanbetova, Sholpan; Sadenova, Marzhan; Mordovtsev, Oleksandr; Tripak, Marian; Dmytriieva, Oksana; Kudriavtsev, Viacheslav; Kudriavtseva, Oksana; Shevchenko, Inna; et al. (PC TECHNOLOGY CENTER, 2025)
The monograph pays attention to the problems and prospects of innovative development of the road and transport complex. In Ukraine, the road and transport complex is classified as a priority system. And taking into account its key role in the defense of the state, the need to carry out scientific developments and practical recommendations for the development of the road and transport system as a whole is becoming urgent.